NK cell cytotoxicity mediated by 2B4 and NTB-A is dependent on SAP acting downstream of receptor phosphorylation - Meinke, Stephan; Watzl, Carsten (Frontiers in Immunology, 2013)
2B4 (CD244) and NK-T-B-antigen (NTB-A, CD352) are activating receptors on human NK cells and belong to the family of SLAM-related receptors. Engagement of these receptors leads to phosphorylation of their cytoplasmic tails and recruitment of the adapter proteins SAP and EAT-2. X-linked lymphoproliferative syndrome (XLP) is a severe immunodeficiency that results from mutations in the SAP gene. 2B4 and NTB-A-mediated cytotoxicity are abrogated in XLP NK cells. To elucidate the molecular basis for this defect we analyzed early signaling events in SAP knockdown cells. Similar to XLP NK cells, knockdown of SAP in primary human NK cells leads to a reduction of 2B4 and NTB-A-mediated cytotoxicity. We found that early signaling events such as raft recruitment and receptor phosphorylation are not affected by the absence of SAP, indicating the defect in the absence of SAP is downstream of these events. In addition, knockdown of EAT-2 does not impair 2B4 or NTB-A-mediated cytotoxicity. Surprisingly, EAT-2 recruitment to both receptors is abrogated in the absence of SAP, revealing a novel cooperativity between these adapters.